Late Republican – early Imperial flat-bottomed amphorae: some remarks about their origins and widespread success - Menchelli , Simonetta; Picchi, Giulia (Rei Cretariae Romanae Fautorum Acta, 2017)
About 25 years ago P. Arthur suggested an Italic origin for the flat-bottomed amphorae model: he maintained that in the Augustan Age in Northern Campania, in the Garigliano basin, precisely in the Masseria S. Donato workshop (located near Suessa Aurunca), Dressel 2–4 bearing the stamp MAESCELS and Dressel 28/Oberaden 74 amphorae were produced side by side. According to the author, these flat-bottomed forms or similar ones were manufactured in the same area as early as the beginning of the 1st century BC as they were found in the ship which sank at Spargi after having set out from Campania.